Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/689521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent behavioral responses in protracted opioid withdrawal in male and female C57BL/6J mice

Abstract: 103)Persons suffering from opioid use disorder (OUD) experience long-lasting dysphoric symptoms well into extended periods of withdrawal. This protracted withdrawal syndrome is notably characterized by heightened anxiety. Here we investigate if an exacerbated withdrawal model of acute morphine dependence results in lasting behavioral adaptation 6 weeks into forced abstinence. We found that our exacerbated morphine withdrawal paradigm produced distinct impairments in elevated-plus maze, open field, and social i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…We found fentanyl exposed mice exhibited increased naloxone precipitated withdrawal signs, suggesting our method produces a degree of opioid dependence. Similar to other studies on protracted opioid abstinence (Bai et al, 2014; Becker et al, 2017; Bravo et al, 2020), we also found decreased social behavior and increased anxiety-like behavior in both sexes of abstinent mice. Since drug exposure canalter HPA axis function (Wemm and Sinha, 2019), we also assessed stress-susceptibility in male mice, using a subthreshold social stressor sometimes termed “microdefeat”(Golden et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…We found fentanyl exposed mice exhibited increased naloxone precipitated withdrawal signs, suggesting our method produces a degree of opioid dependence. Similar to other studies on protracted opioid abstinence (Bai et al, 2014; Becker et al, 2017; Bravo et al, 2020), we also found decreased social behavior and increased anxiety-like behavior in both sexes of abstinent mice. Since drug exposure canalter HPA axis function (Wemm and Sinha, 2019), we also assessed stress-susceptibility in male mice, using a subthreshold social stressor sometimes termed “microdefeat”(Golden et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the symptom expression was positively associated with the number of heroin infusions the animal took at the beginning of the study. Studies in which animals received forced opioid injections have reported hormone abnormalities (Li et al, 2010), persistent anxiety (Bravo et al, 2019), sleep disturbance (Khazan & Colasanti, 1972), and increased motivation to seek heroin (Bossert et al, 2016; Shen et al, 2011) during the protracted period. These behaviors were not fully examined here and would be important next steps to be explored using this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…We know little about how opioid withdrawal differentially affects the sexes in rodent models. However, we do know male and female mice experience withdrawal differently, evident in both their behavior responses and the neurobiology [5,27]. Opioid related sleep disturbances can worsen both pain and withdrawal symptoms.…”
Section: Introductionmentioning
confidence: 99%